Peran Kepercayaan Merek dalam Hubungan Pemasaran dan Loyalitas Konsumen Fast Fashion - Tachaputri Ramadhana Anas; May Roni; Prasetya Nugeraha (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
This study examines the mediating role of brand trust in the relationship between Community Relationship Marketing (CoRM), Customer Relationship Marketing (CRM), and Brand Loyalty among Uniqlo consumers in Indonesia, a fast-growing fashion market driven by consumers who value personalized experience, strong community, and long-term brand engagement. Using quantitative approach, primary data were collected from a sample of 97 Uniqlo consumers through a structured questionnaire and analyzed with Partial Least Square Structural Equation Modeling (PLS-SEM) in SmartPls. Both CoRM and CRM have a significant positive effect on brand trust and brand loyalty, brand trust significantly and positively affects brand loyalty, and brand trust partially mediates the effect of both relational marketing strategies on brand loyalty. The strongest structural effect is the CRM - Brand Trust path (β = 0.546), indicating that direct customer engagement is the most powerful mechanism for building consumer trust. To sustain customer trust and loyalty in Indonesia's highly competitive fashion market, Uniqlo should strengthen customer-centric and community-based relationship marketing strategies.